Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2018) - King, Andrew M. Q.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Adams, Michael J.; Dutilh, Bas E.; Gorbalenya, Alexander E.; Harrach, Balázs; Harrison, Robert L.; Junglen, Sandra; Knowles, Nick J.; Kropinski, Andrew M.; Krupovic, Mart; et al. (Archives of virology, 2018)
This article lists the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses in February 2018. A total of 451 species, 69 genera, 11 subfamilies, 9 families and one new order were added to the taxonomy. The current totals at each taxonomic level now stand at 9 orders, 131 families, 46 subfamilies, 803 genera and 4853 species. A change was made to the International Code of Virus Classification and Nomenclature to allow the use of the names of people in taxon names under appropriate circumstances. An updated Master Species List incorporating the approved changes was released in March 2018 ( https://talk.ictvonline.org/taxonomy/ ).